Implementation of Good Corporate Governance Principles and the Role of Notaries in the Decision-Making Process of the Board of Directors and General Meeting of Shareholders in Indonesia - Putri, Zalfa Fakhriyah Yusov; Nindya, Shelby Padma; Sapyudi, Kathlina; Gultom, Elisatris (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This study examines the implementation of Good Corporate Governance (GCG) principles in the decision-making processes of corporate Boards of Directors and General Meetings of Shareholders (GMS) in Indonesia, focusing on the strategic role of notaries in ensuring legal compliance and enforcement of these principles. The research employs a normative juridical approach by analyzing relevant laws and regulations (including Law No. 40 of 2007 on Limited Liability Companies and the Notary Position Law) and scholarly literature. This normative analysis aims to understand the extent to which GCG norms are operationalized in practice through Board and GMS decision-making mechanisms. The findings highlight that while GCG principles are institutionalized in Indonesian corporate law, practical challenges persist: minority shareholders are often marginalized and decision-making processes can lack transparency. Notaries serve as neutral officials who document and legitimize Board and GMS decisions through authentic deeds, providing legal certainty and traceability. Their oversight and advisory functions contribute significantly to transparency and accountability in corporate governance. The study also identifies that some corporate practices, such as treating the GMS as a mere formality and unilateral decision-making by directors, undermine the objectives of GCG. The conclusion emphasizes that effective GCG implementation requires strengthened notarial supervision and regulatory mechanisms to protect shareholder rights and legal compliance. This article contributes by clarifying the critical role of notaries in operationalizing GCG norms in Indonesia and by recommending policy enhancements to fortify corporate governance practices.